Role of Local Government in Implementing Low Carbon City in Shah Alam - Azhar, Farah Nadia; Mohd Zain, Zarina; Ayob , Nor Azira (Environment-Behaviour Proceedings Journal, 2024)
Low Carbon City Framework (LCCF) provides a guideline for local government to plan new strategies in reducing the carbon footprint to achieve sustainable development goals in Shah Alam, Selangor. This paper aims to examine the local government’s role in reducing carbon emission for the benefit of the community. This study prepares a qualitative approach through semi-structured interviews. The findings found that the success of converting Shah Alam into a low carbon city, requires effective strategies which includes raising awareness, developing an action plans, and implementation and continuous improvements. Through these, the success of local government can be identified in terms of economy, social and health.